Mainstreaming Human Immunodeficiency Virus (HIV) Insurance in India: Opportunities and Challenges - Mayur Trivedi; A. Venkat Raman (ACHSM, 2017)
Millions of Indians fall into poverty because of the private high Out of Pocket pattern of health financing, due to the absence of insurance coverage. Conditions like HIV and AIDS also influence poverty due to a lifelong treatment requirement. Access to insurance coverage (commercial or voluntary) has been denied to People Living with HIV (PLHIV) through various clauses. However lately, there have been certain experiments on inclusion of HIV into new or existing schemes. This paper provides a systematic review of coverage, managerial and financial systems of selected cases of HIV insurance pilots in India with an objective to explore its sustainability and ability to be replicated. A cross-sectional descriptive analysis of existing literature and in-depth case studies of relevant health insurance schemes were used for the review. Data was compiled using qualitative data collection tools such as in-depth interviews with officials. The schemes were analysed using two frameworks viz. managerial ability and coverage ability. The managerial ability was analysed through a Strength-Weakness-Opportunity-Threat (SWOT) analysis. The coverage ability was analysed through three dimensions viz. a) breadth b) depth and c) height. In India, there are two types of insurance policies vis-à-vis HIV coverage. These were categorised as HIV-specific and HIV-sensitive policies. Of the seven pilot schemes reviewed, the small-scale health insurance schemes show limited success owing to smaller pool and limited managerial capabilities. The large schemes offer avenues for mainstreaming but pose issues of governance as well as marketing among PLHIVs. The findings of the research identify a specific set of issues and challenges for sustainability and replication from three perspectives viz. a) market, b) cost recovery and sustainability and c) equitable coverage. Abbreviations: AIDS - Acquired Immune Deficient Syndrome; ART - Anti-retroviral Therapy; BPL - Below Poverty Line; FF-HIP - Freedom Foundation Health Insurance Policy; HIV - Human Immunodeficiency Virus; IRDA - Insurance Regulatory and Development Authority; NGO - Non Government Organisation; PLHIV - People Living with HIV; OI - Opportunistic Infections; OOP - Out of Pocket; RSBY - Rashtriya Swasthya Bima Yojana; STI - Sexually Transmitted Infection; SWOT - Strengths, Weaknesses, Opportunities, Threats; UHC - Universal Health Coverage; UNDP - United Nations Development Program.